Mechatronic positioning system with the velocity control - Drumea, Petrin; Comes, Mircea; Mirea, Adrian; Dobrin, Dănică (Видавництво Національного університету "Львівська політехніка", 2002)
This paper presents a mechatronic system for speed control in non-ferrous continuos foundry machine. This system uses a hydraulic cylinder with inductive displacement transducer, a proportional valve and an electronic module. The moving control uses a positioning closed loop. The electronic block assures position and velocity control and the stop time, too. The cylinder’s displacement is cyclical due an automatic programmer that commands the fastening cylinder, too. User can program both directions’ speed, stroke and pause time. A smooth starting move is assured by acceleration control. The electronic control module is placed in case of proportional element. The program unit contains 8 multi-turn potentiometers for setting motions program, start/stop switch and light Indicator of moving status.